A simple flow injection-reduced volume column system for hemoglobin typing - Srisawang B. (2014)
A flow injection (FI)-reduced volume column system was developed for hemoglobin (Hb) typing to be used as an initial screening method for thalassemia. The column was packed with 140 μl diethylaminoethyl (DEAE)-Sephadex A-50 ion exchange beads. Hb can be separated using Tris-HCl buffer solution with pH gradient 8.5-6.5 and then monitored spectrophotometrically at 415 nm. The hemolysate of 40 blood samples from packed red cells were screened for thalassemia by determining the amount of HbA2 and HbE present. The proposed system was able to predict positive test results from those samples with β, E-trait and EE homozygous thalassemia, Hb types that were independently identified following the conventional method at the hospital laboratory. Advantages of the proposed system over the conventional column technique include low amount of reagents and blood sample needed, short analysis time and low cost. Each analysis required only 80 μl of 50 times diluted packed cells, which is equivalent to 1.6 μl undiluted packed cells, and it can be completed in only 35 min. This simple FI-reduced volume column system was demonstrated to be an economic alternative system for Hb typing to initially screen some types of thalassemia such as β-trait, E-trait and EE-homozygous which are commonly found in Thailand. © 2003 Elsevier B.V. All rights reserved.